Management and simultaneous implant placement of maxillary sinus membrane perforation: A report of two cases - Mangesh Phadnaik; Ripunjay Kumar Tripathi; Meghna Nigam; Ankit Solanki; Vaibhav Karemore (Wolters Kluwer Medknow Publications, 2020)
Rehabilitation of the long-standing edentulous posterior maxilla with dental implant poses a unique challenge. This is due to mainly two reasons - pneumatization of the maxillary sinus and atrophy of the alveolar bone. The challenge is intensified when the native bone is around 2-3 mm. This requires vertical bone augmentation in the form of direct sinus lift/lateral wall sinus lift procedure. The most common complication associated with this procedure is the sinus membrane perforation resulting in unfavorable stabilization of the graft and associated bone regeneration. Simultaneous implant placement becomes all the more difficult in such situations. As a result, of which implant placement has to be deferred resulting in extended treatment duration and multiple surgical appointments. The present case report represents two such sinus membrane perforation repair cases associated with lateral wall osteotomy approach for sinus augmentation with simultaneous implant placement in the posterior maxilla.